Perusing Public Services in Religious Affairs Office: A Study of Responsive Governance - Nur, Mohamad Ichsana (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2024)
There has been a transformation of the public service sector at the Office of Religious Affairs in Indonesia, which was initially undertaken manually to become digital in order to improve more responsive services. This study aims to analyze the public services of the Office of Religious Affairs (KUA) in West Java Province from the perspective of Responsive Governance. This study uses a quantitative approach. This research uses a descriptive type of research. The locus taken in this study was the Office of Religious Affairs (KUA) in West Java Province. Technically, the researchers will divide it into four different clusters spread across the East, West, North, and South of West Java. In this study, primary data was obtained through the distribution of questionnaires. Secondary data is obtained through several studies of documents and other published materials, such as journal articles, theses, dissertations, research reports, other textbooks, and official office documents, such as annual reports, statistical reports, and other appropriate official documents. This study indicates that the implementation of public services at the Office of Religious Affairs in many areas of West Java Province can be said to be heading in a responsive direction. This research concludes that if the public service of the Office of Religious Affairs does not pay attention to the principle of responsiveness, given the development of an increasingly modern and dynamic era, it will have an impact on the emergence of dissatisfaction and even public skepticism.